Peran Pekerja Sosial dalam Implementasi Program Griya Pesantren Lansia Juara di Unit Pelaksana Teknis Daerah Pusat Pelayanan Sosial Griya Lansia Ciparay Kabupaten Bandung - Sugiansyah, Ratna Nurkhalika; Yuliani, Dwi; Haryani , Ayi (Politeknik Kesejahteraan Sosial Bandung, 2023)
This research aims to gain a clear about social worker’s role in facilitating the fulfillment of spiritual needs for elderly, social worker’s role in provide assistance to spiritual development for elderly, and social worker’s role in provide consulting services based on elderly needs. This research used qualitative approach with descriptive method. Informants were determined based on purposive sampling. Informants in this research amounted to 10 persons such us 2 persons of elderly, 6 persons of social worker, and 2 persons of staff. Data collection techniques used indepth interview, participatory observation and study of documentation. The results of this research showed that social worker have some role in implementation pesantren lansia juara program. Social worker’s role in facilitating the fulfillment of spiritual needs for elderly as social planner, coordinator, and fasilitator. Social worker’s role in provide assistance to spiritual development for elderly as borderer and fasilitator. Social worker’s role in provide consulting services based on elderly needs as counselor and motivator. There are some obstacles in implementation pesantren lansia juara program such us inconsistency social workers with their proper duties and functions, inter-professional coordination in implementation pesantren lansia juara program is lacking, and social workers doesn’t record in implementation pesantren lansia juara program. Based on the results of this research, the researcher proposed “Peksos Juara to Optimize in Implementation Pesantren Lansia Juara” program uses social groupwork methods with discussion techniques.